Evaluasi SIMRS Pada Bagian Registrasi Pasien Di RSUD Drs. H. Abu Hanifah Menggunakan Metode TAM - Suriani; Atma Deharja; Maya Weka Santi; Andri Permana Wicaksono (Manajemen Pelayanan Kesehatan, 2024)
The implementation of the Hospital Management Information System (HMIS) in patient registration at RSUD Drs. H. Abu Hanifah, Central Bangka Regency, encountered several issues. These included a 22.30% delay in the transmission of inpatient data in November 2022 due to unstable internet connections, a lack of user guidance, slow patient data retrieval, and frequent system errors. These problems decreased the registration staff's willingness to use HMIS. This study aimed to evaluate the use of HMIS in patient registration using the Technology Acceptance Model (TAM). The research employed a qualitative design, collecting data through interviews, observation, documentation, focus group discussions, and brainstorming sessions. The subjects of the study included 1 Head of the Medical Records Installation, 1 IT staff, and 6 registration staff. The results indicated that not all registration staff had received training on HMIS, there was no HMIS user manual available, the registration staff were unaware of the policies and SOPs for using HMIS, and the internet quality was often unstable. The suggested solutions included training for all registration staff, the creation of a HMIS user manual, distribution of copies of HMIS implementation policies and SOPs, and upgrading the equipment used to operate HMIS.